1996
DOI: 10.1179/sur.1996.12.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contaminants on gas nitriding

Abstract: Machining of steels not only affects the shape of the workpiece, but also influences surface structure and composition. At elevated temperatures and pressures during machining or the subsequent cleaning process cooling lubricants, hydraulic oils, machine greases, and cleaning residues can form stable adsorption or reaction layers. These layers can work as barriers and therefore inhibit surface modification reactions, as can be seen in the example of gas nitriding. The aim of the present investigation was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The work carried out by Irretier et al also showed that a pre-oxidation of 30 min in air improved the mechanical properties after nitriding in the case of 42CrMo4-grade steel, and inhibited these mechanical properties in the case of C15 and X155CrMoV12.1 grade steels [24]. Neither of these results is in agreements with the present work.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 3 more Smart Citations
“…The work carried out by Irretier et al also showed that a pre-oxidation of 30 min in air improved the mechanical properties after nitriding in the case of 42CrMo4-grade steel, and inhibited these mechanical properties in the case of C15 and X155CrMoV12.1 grade steels [24]. Neither of these results is in agreements with the present work.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…It should be considered that the pretreatment parameters can influence the layer formed. Irretier et al prepared the samples with a very low partial oxygen pressure (5.7 10 -23 Pa) [24], while the oxidation process was carried out, in this work, with a partial oxygen pressure of approximately 13 10 3 Pa. As a consequence, it can be assumed that the layer formed during the present work is thicker than the one obtained in the reference, leading to a non-negligible reduction duration, and so, a…”
Section: Accepted Manuscriptmentioning
confidence: 87%
See 2 more Smart Citations